Drug utilization pattern of analgesics as a teaching tool for rational therapy to MBBS students in a medical college at Dehradun, Uttarakhand, India - Beg, Mirza Atif; Dutta, Shakti B.; Bawa, Shalu; Kaur, Amanjot; Vishal, Subhash; Kumar, Upender (International Journal of Basic & Clinical Pharmacology, 2017)
Background: As a need to introduce Clinical Pharmacology at the undergraduate level the drug utilization studies (DUS) offer useful methods for teaching and training in drug therapy. The indiscriminate use of medicines results in unwanted side effects, drug interactions. Thus keeping this view in mind, this drug utilization research was set to evaluate the prescribing pattern of analgesics to impart certain basic skills to MBBS students which will form an integral component of practicing rational therapeutics. Methods: The retrospective study was conducted by Pharmacology department in SGRRIM and HS. A total of 726 prescriptions were collected by 2nd professional MBBS students entering 5th semester and randomly evaluated for prescribing pattern using WHO drug use indicators. Results: A total of 726 prescriptions were analyzed. Male:Female ratio was 470:256(1.8:1). Age wise distribution of patients 0-15years 122(16.80%), 16-30 years 139(19.41%), 31-45years 242 (33.33%), 46-60 years 113(15.56%) and >60years 110 (15.15%). A total of 4663 drugs were prescribed. 435(9.32%) were analgesics. 208 (47.81%) Paracetamol, 66 (15.17%) Tramadol, 62(14.25%) Aceclofenac, 51 (11.72%) Diclofenac, 46 (10.57%) Ibuprofen and 2(0.45%) Buprenorphine were prescribed. 301 (69.20%) Oral drugs and 134 (30.80%) Injectable were prescribed. 108 (24.83%) Numbers of Fixed dose combinations. 0.60 of analgesics were prescribed per prescription. 381 (87.59%) analgesics were prescribed from National Essential Medicine list 2015. 369 (84.83%) drugs were prescribed by brand names. Conclusions: The main purpose of undergraduate medical curriculum is to develop the requisite diagnostic and therapeutic skills of a basic doctor. Such type of drug utilization studies is set with the objective to encourage rational prescribing, and to identify good and bad prescribing practices.